Innovations and Strategies for Logistics and Supply Chains: Technologies, Business Models and Risk Management - Wolfgang Kersten; Thorsten Blecker; Christian M. Ringle (epubli GmbH, 2015)
The HICL-Conference celebrates its 10th anniversary, indicating major interest in the research fields of supply chain management and logistics. They are dedicated to make recommendations for new approaches and solutions that enable companies to cope with current and future challenges in supply chains and logistics. The first volume of the 2015 conference addresses innovative and technology-based approaches for logistics and supply chains. It presents business models and investment options for enhanced strategic decision making as well as recent approaches for supply chain risk management.
urn:nbn:de:gbv:830-88213472; https://econpapers.repec.org/RePEc:zbw:hiclch:209249; https://econpapers.repec.org/RePEc:zbw:hiclch:209250; https://econpapers.repec.org/RePEc:zbw:hiclch:209251; https://econpapers.repec.org/RePEc:zbw:hiclch:209252; https://econpapers.repec.org/RePEc:zbw:hiclch:209253; https://econpapers.repec.org/RePEc:zbw:hiclch:209254; https://econpapers.repec.org/RePEc:zbw:hiclch:209255; https://econpapers.repec.org/RePEc:zbw:hiclch:209256; https://econpapers.repec.org/RePEc:zbw:hiclch:209257; https://econpapers.repec.org/RePEc:zbw:hiclch:209258; https://econpapers.repec.org/RePEc:zbw:hiclch:209259; https://econpapers.repec.org/RePEc:zbw:hiclch:209260; https://econpapers.repec.org/RePEc:zbw:hiclch:209261; https://econpapers.repec.org/RePEc:zbw:hiclch:209262; https://econpapers.repec.org/RePEc:zbw:hiclch:209263; https://econpapers.repec.org/RePEc:zbw:hiclch:209264; https://econpapers.repec.org/RePEc:zbw:hiclch:209265; https://econpapers.repec.org/RePEc:zbw:hiclch:209266; https://econpapers.repec.org/RePEc:zbw:hiclch:209267; https://econpapers.repec.org/RePEc:zbw:hiclch:209268; https://econpapers.repec.org/RePEc:zbw:hiclch:209269
Keywords: 650; Logistics; Supply Chain Management; Supply Chain; Supply Chain Risk Management; Technology Management; Strategic Decision Making; Innovation